The Influence Of Principal Leadership And Instructional Supervision On Improving The Professional Competence Of Teachers During The Covid-19 Pandemic At State High School (SMAN) And The State Vocational High School (SMKN) In Malang City - Prestiadi, Dedi; Zulkarnain, Wildan; Nurabadi, Ahmad; Ubaidillah, Endra; Mauilana, Fuad; Mustabsyiroh, Nurul (Universitas Negeri Malang, 2022)
This study aims to determine the influence of the principal's leadership on teacher professionalism, the influence between instructional supervision on teacher professionalism and the simultaneous influence of principal leadership and instructional supervision on teacher professionalism. This research was carried out at the State High School (SMAN) and the State Vocational High School (SMKN) in Malang City as a research population, as sampling was carried out through purposive random sampling. The research method uses a quantitative approach, namely to see the partial influence between existing variable variables. This study uses a regression analysis that aims to determine the influence between independent variables on dependent variables. The independent variables in this study are principal leadership (X1) and principal supervision (X2), while the dependent variables are teacher professional competence (Y). The result of this study is that there is a simultaneous relationship between the leadership of the principal and the supervision of learning to the professionalism of teachers at State High School and the State Vocational High School in Malang City. The degree of influence can be categorized at a strong level, this is known from the magnitude of the correlation coefficient value of 0.862 which means it has a strong category. Meanwhile, the variable influence of principal leadership and instructional supervision had an influence of 74.3% on teacher professionalism.